2018
DOI: 10.4236/jwarp.2018.102011
|View full text |Cite
|
Sign up to set email alerts
|

Low Flow Trends and Frequency Analysis in the Blue Nile Basin, Ethiopia

Abstract: Low flow analysis provides crucial information for the planning and design water resource development, risk assessment and environmental flow management. Understanding the low flow regimes and evaluating the magnitudes for incorporating in water resources management is vital for the countries like Ethiopia where demand for water is increasing. However, there were hardly enough studies in understanding the trends of low flow and frequency analysis. Therefore, this study focuses on evaluation of the trends in lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The Mann-Kendall non-parametric statistical test (M-K test) can effectively detect variations in hydrological data over time, and has been widely employed in the fields of hydrology and climate [34][35][36]. The method assumes a stable time series, and a random independence of the time series is required.…”
Section: Mann-kendall Trend Testmentioning
confidence: 99%
“…The Mann-Kendall non-parametric statistical test (M-K test) can effectively detect variations in hydrological data over time, and has been widely employed in the fields of hydrology and climate [34][35][36]. The method assumes a stable time series, and a random independence of the time series is required.…”
Section: Mann-kendall Trend Testmentioning
confidence: 99%
“…For instance, the change of the forest to agricultural land could largely increase runoff in the rainy season and recovery of heavy rainfall after the year 1990 in West Africa. This has been indicated in different studies such as (Descroix et al, 2013;Sighomnou et al, 2013;Cissé et al, 2014;Panthou et al, 2014;Yao, 2015;Kouamé, 2017;Assefa & Moges, 2018). In addition, analyses using the Mann-Kendall statistical test showed that 50 to 67% of low-flow series do not show significant trends in variance.…”
Section: Low Flow Trend Analysis Resultatmentioning
confidence: 72%
“…Evaluating the presence and absence of trends in low flow for the selected stations were carried out by using the Mann and Kendall (MK) trend test (Kendall, 1975 presence of the monotonic increasing/decreasing trend. This statistical test has a variety of applications for trend analysis (Temesgen et al, 2014;Assefa & Moges, 2018;Thomas et al, 2019). The non-parametric Mann-Kendall statistical test has been affected and the most used to assess the significance of the trend in low-flow indices.…”
Section: Mann-kendall Trend Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The (UBNRB) is the part of the watershed of the Blue Nile River Basin which is the source of water for major irrigation schemes in Sudan and contributes about 60-69% of the Nile's annual flow (Conway, 2000;Tabari et al , 2015). The area of the basin is represented 199,812 km 2 and lies in three national regional states where 46% of the basin area is Amhara, 32% in Oromia and 22% in Binishangul-Gumuz (Assefa and Moges, 2018). The UBNRB represents an essential water resource for Ethiopia and for the downstream countries Sudan and Egypt as well.…”
Section: A Study Area and Data Setmentioning
confidence: 99%